Trends in the frequency of obesity in women of childbearing age. Study based on the Encuesta Nacional Demográfica en Salud (ENDES), Peru, 2005-201 - Hoppe , Wolfgang (2024)
Objective: To describe the trends in the frequency of obesity and its relationship with some socioeconomic factors in women of childbearing age in Peru. Methods: Analytical cross-sectional study of secondary data, using the databases of the Encuesta Nacional Demográfica en Salud (ENDES) from 2005 to 2018. The frequency of women with obesity was estimated for each year and compared using the confidence intervals at 95% (95% CI). The magnitude of association was compared between place, age and parity, place of residence, level of education and wealth index. Results: An increase in obesity was observed in women of childbearing age from 17.72% (95% CI: 16.24-19.32) in 2005 to 32% (95% CI: 30.46-34.42) in 2018. The prevalence of type I obesity increased from 9.07% (95% CI 8.09-10.16) in 2005 to 22.15% (95% CI 15.19-16.48) in 2018. It was observed a continuous increase in the prevalence of type II obesity from 2.34% (95% CI 1.84-3.05) to 7.29% (95% CI 3.75-4.52). In women who were pregnant at the time of the interview, a prevalence of obesity was found to be 17.21% (95% CI 11.42-25.10) in 2005, reaching 38.61% (95% CI 20.25). -28.46) in 2018. A significant relationship was found between the possibility of being obese with age and parity. Conclusions: The prevalence of obesity in women of childbearing age in our country is high and continues to increase over time. The increased prevalence also occurs in pregnant women, increasing maternal-perinatal complications.